Notch-free vermillion after unilateral cleft lip repair: The Charles Pinto centre protocol - Narayanan P; Adenwalla H (Indian Journal of Plastic Surgery)
A notch on the vermillion is one of the most common complications following the repair of a unilateral cleft lip. Several methods have been described for the secondary correction of a notch. However, there are only a few reports on how the notch can be prevented during primary lip repair. Causes of a vermillion notch were analysed at the Charles Pinto Centre for Cleft Lip and Palate and each possible cause addressed by an appropriate procedure. This protocol was then followed in every patient. In this manner, we have been able to avoid notches in unilateral cleft lips altogether and more significantly, junior trainees in our department have also been able to consistently avoid a notch in their repairs.